Effect of Irradiated Rice Varieties on CH4, Population of Bacteria and Fungi in tidal Swamp Soil in Kalimantan. Issue 1 (June 2020) - Hadi, Abdul; Zahrita,; Haris, Abdul
Abstract: Recently, paddy fields have encountered extreme environmental conditions like flood and storm which caused decreased grain production. To overcome this problem, National Atomic Energy Agency (BATAN) of Republic of Indonesia has developed hybrid rice varieties like Atomita, Sulutan Unsrat, Woyla, etc. However, there are few reports on population of bacteria, fungi, and the methane (CH4 ) emissions as affected by these rice varieties in tidal swamp area of Kalimantan. A field experiment has been carried in tidal swamp of South Kalimantan aiming at elucidating the effect of irradiated rice varieties on CH4, population of bacteria and fungi. Sixteen plots, each sizing 3 m x 4 m, were demarcated by plastic tape. At the same time with land preparation, rice varieties of Atomita (irradiated), Sulutan Unsrat (irradiated), Woyla (irradiated) and Karang Dukuh (local variety) were nursed in nearby upland until one month old. Three of the plots were cultivated to Atomita rice variety, three of the plots were cultivated to Sulutan Unsrat rice variety, while the other three were cultivated to Woyla rice variety. The rest of the plots were cultivated to Karang Dukuh and considered as control treatment. Air samples were collected by closed chambers in biweekly bases until harvest of rice. Air samples were then transferred to laboratory and used for the determination of CH4 concentration. Soil samples were taken at 15, 45, 75 and 105 days after transplanting and used for determinations of bacterial and fungal numbers using plate count method. The results showed that irradiated rice varieties suppressed CH4 emissions from tidal swamp paddy filed. More suppression was given by Sulutan Usrat, while Atomita and Woyla gave similar affects. There were no differences in population of bacteria in the four rice variety except at 15 days after transplanting when Atomica gave highest number. Similarly, there was no difference in population of fungi in the four rice variety except at 45 days after rice transplanting when Sulutan Unsrat gave highest number. These suggest that irradiated rice varieties suppressed CH4 emissions without negative impact on the bacterial and fungal population in tidal swamp soil of Kalimantan.